Religiosity and Muslims’ intention to visit homestays: the mediating role of attitude - Azrin Bin Jalasi; Sylvia Nabila Azwa Ambad (Goodwood Publishing, 2020)
Purpose: This study aims to examine the influence of religiosity and attitude on the Malaysian Muslims’ intention to visit homestays in Sabah. Also, attitude is tested as a mediator in the hypothesized relationship. Research Methodology: A quantitative cross-sectional approach was applied to gather data from a sample of 251 Malaysian Muslims, and a convenience sampling method is employed to collect data for the study. Data collected were analysed using SmartPLS 3.3.2.9 software. Results: The findings indicate that religiosity and attitude significantly influence the Malaysian Muslims’ intention to visit homestays in Sabah. Additionally, the relationship between religiosity and the Muslims’ intention to visit the homestays are mediated by attitude. Limitations: The scope of the study is limited to Malaysian Muslims’ intention to visit homestays in Sabah only. Contribution: The study provides empirical evidence for the individual factor that attitude significantly mediated the linkage between Muslim’s religiosity and their intention to visit homestays. As for practical implication, the study’s findings should instigate the improving and enhancing of the homestays’ services in Malaysia according to the Islamic principles in the future. Keywords: Muslims, Intention, Attitude, Religiosity, Homestay visit